PENGARUH KEPEMIMPINAN, MOTIVASI, DAN KOMUNIKASI TERHADAP KINERJA PEGAWAI DI PT.PLN (Persero) APJ SEMARANG - Nanik Yuni Puspitosari, 10.05.51.0011 (Students Journal of Economic and Management, 2014)
This studyanalyzed the effects ofwork motivation, leadership, work environmenton employee performance. The research objectin this paper isPT.PLN (Limited) APJ Semarang. Sampling technique in this study is the use of purposive sampling of 100 respondents in the sample by using the method of data collection questionnaire (questionnaire) by distributing a list of questions to respondents in order to obtain information. The purpose of the study was formulated to determine the effect of leadership, motivation, communication on employee performance. The data were analyzed using factor analysis to test the validity of the question items, Cronbach alpha formula to test the reliability of the instrument, regression analysis, to examine the influence of each partial independent variables were tested by regression analysis. The results of the research are: (1) Leadership has a positive and significant impact on employee performance. (2) Motivation does not have an influence on employee performance. (3) Communication has a positive and significant impact on employee performance. Keywords: work leadership, motivation, communication and employee performance.